La necesidad de establecer el acoso laboral como causal o motivo de despido intempestivo en el código de trabajo - Chancusig Unatambo, Juan Pablo (2015)
The present so called thesis project: "THE NEED TO ESTABLISH THE LABOR HARASSMENT(HOUNDING) AS GROUNDS OR MOTIVE OF UNTIMELY DISMISSAL IN THE CODE OF WORK”, which(who) represents a problems of current and daily interest reason for which it influences in the newspaper to live of the persons. Nevertheless to more of it, on having spoken to him about labor harassment (hounding), one is touching conflicts that in the first instance turn out to be shown in the hearth, coming in most cases to familiar (family) ruptures, not without earlier happening (passing) for the depression of those who have been an object or victims of the labor harassment (hounding). During the history of our country many changes of the laws have existed you will work being witnesses of all you reform it to this juridical norm, which(who) are directed to look for the well-being(comfort) of the hard-working class and its family circle, nevertheless at present in the labor legislation still there keep on existing legal gaps which create conflicts the same ones that damage the rights of the workpeople or workers as it is the stability, the personal integrity and a sin number of fundamental rights that during of the development of the present thesis we will be able to be demonstrating. In our Constitution in the art. 33 shows that the work is a right and a social duty and that the State will be who guarantees to the workpeople in general the full respect to its dignity(rank), rights that must be respected for this way this way to Live is fulfilled by the Constitutional Beginning of the Good one, The absence of regulation and alertness, the abuse of authority and the labor harassment (hounding) are the forms that the employer uses to give for finished the labor relation, reasons that in totalitarian form damage the rights of the workpeople and contradicting the order of the people, taken shape of the Constitution of 2008, therefore a law reform is urgent to the code of the work to prevent the rights of the workpeople who have been damaged on the part of the employers.